The Kenya Livestock Insurance Program (KLIP) improved drought mitigation and enhanced food security for over 20,000 pastoralist households in 2017. - CGIAR Research Program on Livestock (2017)
KLIP, a Government of Kenya funded drought insurance program, paid out Kshs. 494 million to 22,000 vulnerable pastoralist households in 2017 alone . These pay-outs ensured that farmers could buy their own food as well as fodder, drugs and water for their livestock during periods of drought. Covering eight counties in Kenya, the program has enabled the beneficiaries to keep their animals alive after the failure of the short and long rains in 2016 and 2017.